Pain characterization in Duchenne muscular dystrophy - Silva, Talita Dias da; Massetti, Thais; Monteiro, Carlos Bandeira de Mello; Trevizan, Isabela Lopes; Arab, Claudia; Caromano, Fatima Aparecida; Voos, Mariana Callil; Oliveira, Acary Souza Bulle; Favero, Francis Meire (Arquivos de Neuro-Psiquiatria, 2016)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder, characterized by progressive muscle weakness. Historically, pain has not been considered to be a major symptom in DMD. Objective To investigate the relationship between DMD and pain.Methods We conducted a systematic review in Medline/PubMed and BVS (virtual library in health) databases. We searched for articles that showed the terms “Muscular Dystrophy, Duchenne” and “Pain” in all fields. All studies included boys diagnosed with DMD and the occurrence/amount of pain on this population.Results Initially, there were 175 studies. 167 articles were excluded for not meeting the inclusion criteria. The remaining eight eligible studies, involving pain assessment in DMD, were analyzed.Conclusion Pain is a frequent problem in this population and this symptom is potentially tractable. Studies conclude that pain can directly influence the quality of life of this population.
Keywords: Muscular Dystrophy, Duchenne; Pain; Neuromuscular Diseases